Journalism and Islam in The Malay Archipelago: Five Approaches - Janet Steele (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2019)
Although the principles of journalism – truth, verification, balance, and independence from power – are arguably universal, they are interpreted through the prisms of local culture. Five news organizations in Indonesia and Malaysia suggest a variety of approaches to understanding the relationship between journalism and Islam. Whereas writers at Indonesia's Sabili magazine were selected based on their experience in the tarbiyah or education movement, at Republika (an Indonesian newspaper established to serve the Muslim community) journalistic skills are more important than outward demonstrations of piety. Muslim journalists at the two most liberal of these publications, Indonesia's Tempo magazine and Malaysia's news-portal Malaysiakini, see their work in substantive rather than scripturalist terms, and editors of Harakah, the newspaper of the Pan- Malaysian Islamic party, are outspoken champions of freedom of expression. These varied approaches suggest there is much to be learned from the influence of Islam on the practice of journalism in Southeast Asia.